Castelao’s Exile in North America (Texts and Documents) - Mejía Ruiz, Carmen (Madrygal. Revista de Estudios Gallegos, 2004)
The purpose of the following research is about Castelao's stay as exile, in New York. Our main approach is concerning Castelao's idea in favour of Spanish Republic and Galleguismo, with his consequent depression. We are trying to open a new way in order to investigate about the Galician exile in North America. Exile, freedom, depression, fight.
Keywords: Exilio; Libertad; Desesperanza; Lucha; Soledad